Direct Detection and Discrimination of Nucleotide Polymorphisms Using Anthraquinone Labeled DNA Probes - Goodchild, Sarah A.; Gao, Rachel; Shenton, Daniel P.; McIntosh, Alastair J. S.; Brown, Tom; Bartlett, Philip N. (Frontiers in Chemistry, 2020)
A novel electrochemical detection approach using DNA probes labelled with Anthraquinone (AQ) as a reporter moiety has been successfully exploited as a method for the direct detection of DNA targets. This assay uses simple voltammetry techniques (Differential Pulse Voltammetry) to exploit the unique responsiveness of AQ to its chemical environments within oxygenated aqueous buffers, providing a specific detection mechanism as a result of DNA hybridisation. This measurement is based on a cathodic shift of the reduction potential of the AQ tag and the concurrent reduction in peak current upon DNA binding. The further utility of this approach for discrimination of closely related DNA targets is demonstrated using DNA strands specific to B. anthracis and closely related bacillus species. DNA targets were designed to the rpoB gene incorporating nucleotide polymorphisms associated with different bacillus species. This assay was used to demonstrate that the shift in reduction potential is directly related to the homology of the target DNA. The discriminatory mechanism is dependent on the presence of oxygen in the measurement buffer and is strongly linked to the position of the nucleotide polymorphisms; with homology at the terminus carrying the AQ functionalised nucleotide critical to achieving accurate discrimination. This understanding of assay design was used to demonstrate an optimised assay capable of discriminating between Yersinia pestis (the causative agent of plague) and closely related species based on the groEL gene. This method is attractive as it can not only detect DNA binding, but can also discriminate between multiple Single Nucleotide Polymorphisms (SNPs) within that DNA without the need for any additional reagents, reporters or processes such as melting of DNA strands. This indicates that this approach may have great potential to be exploited within novel biosensors for detection and diagnosis of infectious disease in future Point of Care (PoC) devices.